GEOTOURISM & GEOMORPHOSITES: THE G.I.S. SOLUTION - Gregori, Lucilia; Melelli, Laura (Alpine and Mediterranean Quaternary, 2005)
L. Gregori & L. Melelli, Geotourism & Geomorphosites: the G.I.S. solution. (IT ISSN 0394-3356, 2005). Geomorphologic research which has the geographical area of Umbria and the neighbouring territories as a subject of study, sheds light on some features possessing a relevant cultural and scientific value, known in literature as “Geomorphosites”. Nowadays Geotourism is an excellent opportunity to exploit the scientific knowledge researchers have of geomorphosites as a source of didactical and economical value. The idea is to enhance the tourist attention towards geomorphosites, through the use of more traditional and better known interests. Having this aim in mind, a more careful research was made for each geomorphosite. Different characteristics are reported as: oenogastronomic tours, historic-artistic values, and craftsmanship activities. G.I.S. are the best instruments to manage and analyze geomorphologic data. In particular geomorphosites, which are mapped and spatially georeferenced have a geographical characterization so that they can be best studied through the use of G.I.S. In G.I.S. different functions are available as querying maps, or building relations in relational database (one to one or many to one) in order to obtain detailed tourist itineraries.